Analisis Kebutuhan Media Pembelajaran untuk Menghafalkan Perkalian bagi siswa SD Kelas IV - Wahyu Tri utami; Ida Dwijayanti; Sumarno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
ABSTRACT During offline learning, teachers and students face problems and obstacles, namely teachers do not understand students’ needs, lack of developing learning media to support students in learning which causes students to not understand the material presented, students have difficulty with learning Mathematics, namely memorizing multiplication, teachers do not use methods and models. varied learning. This research aims to analyze the need for media used to support memorizing multiplication. This research was a qualitative descriptive study conducted at SDN Rakitan, Sluke District, Rembang Regency. Data collection used was interviews and observation. Based on the results of interviews and observations, it is known that students have difficulty understanding and memorizing multiplication. Apart from that, teachers still have not found a learning design that suits the characteristics and needs of students. The results of interviews and observations with class IV students and teachers showed that 75% of students did not like and had difficulty understanding and memorizing multiplication. Meanwhile, in interviews and observations of teachers, it was found that there were students who did not memorize multiplication at all, they couldn’t even do multiplication by 2. Based on the results of the analysis of learning media needs, it can be seen that teachers and students need learning media to memorize multiplication to support mathematics learning.